GIS-material for the archaeological project: Ledberg-Lärbo - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
By request of the County Administrative Board in Östergötland and due to laying of an electric cable, the Swedish National Heritage Board's Contract Archaeology Division, UV Öst, has performed an archaeological assessment, phase 2, within the properties Ledberg 10:1 and Lärbo 3:6, Ledberg parish, Linköping municipality. The survey verified that there are remains of prehistoric activity within the area, although no further archaeological measures are needed as the cable laying does not affect the remains to any great extent.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the assessment was to determine whether any archaeological remains were going to be affected by the planned development works.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På uppdrag av Länsstyrelsen i Östergötland har Riksantikvarieämbetet UV Öst utfört en arkeologisk utredning, etapp 2, inom Ledberg 10:1 och Lärbo 3:6, Ledbergs socken, Linköpings kommun. Utredningen föranleddes av en planerad jordkabelförläggning. Den arkeologiska utredningen konstaterade att det inom den aktuella exploateringsytan finns spår av förhistoriska aktiviteter. Då kabelnedläggningen inte gör någon större åverkan på de befintliga fornlämningarna, får vidare åtgärder inte anses vara nödvändiga. Undersökningsytan bedöms därmed ur arkeologisk synvinkel vara klar för exploatering.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen, etapp 2, var att utröna om en fast fornlämning berörs av det planerade exploateringsprojektet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Ledberg-Lärbo
Keywords: stone age; stenålder; Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi